Evaluasi Pemajakan Atas Nilai Tambah dalam Biaya Angkutan Laut dan Udara (Freight) Kargo pada Perusahaan Freight Forwarding di Indonesia - Chairil Anwar Pohan; Pebriana Arimbhi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
Enactment of the application of the tax base in the form of Other Values for Freight Charges has become a smart "breakthrough" of the basic principles and tax characteristics contained in the VAT and VAT mechanism, and this policy is considered "successful" raised a complicated issue contained in the aspect fiscal (theoretical concept to aiming the difference in freight) when in fact there is no urgency or complicated issue from the fiscal aspect that requires to "other value" the freight charges for the calculation/imposition of VAT on freight charges in the delivery transaction of Freight Forwarding Services. Although taxpayers make a "breakthrough" of taxation on freight that has been considered "untaxable" beforehand, but on the other side, it is unfortunately the concept of taxation based on Regulation Finance Minister no. 38 / PMK.011 / 2013 on amendment to Regulation of the Minister of Finance no. 75 / PMK.03 / 2010 concerning other Values may cause losses for state revenues, because the VAT mechanism is disrupted due to theoretical concept of the tax base has not effectively being aiming. From the point of view of revenue productivity principle, the concept raises a new problem that really does not need to happen because basically the realization of the transactions of freight differences that can be "captured" from commercial bookkeeping held based on the applicable Financial Accounting Standard is an indication of the creation of an added value that become the object of VAT imposition. The application of the tax base in the form of Other Values for Freight Charges has "damaged" the value of the basic principles and tax characteristics contained in the VAT and VAT mechanism by means of to "other value" such freight charges for VAT calculation/imposition of VAT on freight charges in delivery transactions of Freight Forwarding Services (JPT / FF).